The survival rate of tuberculosis patients in HIV-treated cohort of 2008-2018 in Almaty, Kazakhstan - Zhandybayeva, Ainur; Truzyan, Nune; Shahumyan, Elina; Kulzhabaeva, Aizat; Nugmanova, Zhamilya; Denebayeva, Alfiya; Tukeyev, Marat (The Journal of Infection in Developing Countries, 2020)
Introduction: HIV/TB comorbidity is responsible for 1.6 million deaths worldwide. HIV/TB control and patients’ survival are still among priorities of the national HIV and TB programs. We aimed to evaluate the HIV/TB survival in connection with TB treatment outcomes and factors influencing life duration of the cohort 2008-2018 in Almaty, Kazakhstan. Methodology: This retrospective cohort study extracted data for all HIV and pulmonary TB adults coinfected during 2008-2018 in Almaty from national registries to apply descriptive, Kaplan-Meier estimation, and Cox proportional hazards regression model. Survival function for the TB treatment outcomes and factors predicting the probability of survival were tested and described. Results: The cohort population (n = 521) mean age was 37.4 years with 405 (77.7%) males and 210 (40.3%) marrieds. More than one TB treatment had 181 (34.7%) patients, 291 (55.9%) were smear-positive (SS+), and 423 (81.2%) were on antiretroviral therapy with mean CD4 count 254.22cells/µL. Probability to live longer was higher (128 versus 37 months, p = 0.003; 95% confidence interval (CI) 71.65, 184.35) for those who succeeded in TB treatment compared to “lost to follow-up” and “failed” treatment outcomes. Adjusted Cox regression model death hazard showed association with missing ART treatment (HR: 1.699, 95%CI 1.164, 2.481, p = 0.006) and having CD4 count < 499 (HR 2.398, 95%CI 1.191, 4.830, p < 0.014). Conclusion: TB treatment outcomes, ART treatment, and the CD4 count of HIV/TB coinfected population substantially influence their life duration. The medical decision- and policy-makers should take this into consideration when implementing targeted improvements in the national HIV and TB programs.